Mexico : 2015 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the economy of Mexico has continued to grow at a moderate pace, and capital outflow pressures have been limited. The flexible exchange rate has helped the economy adjust to external shocks, while inflation has remained low and stable. Mexico is implementing a broad range of structural reforms, which should help lift potential growth over the medium term. The economy is projected to grow by 2.25 percent in 2015. Construction activity has moderated after a strong rebound in the second half of 2014. Manufacturing and services remain the main driver of growth, although weaker-than-expected U.S. demand affected manufacturing exports in early 2015.